PENGELOLAAN RETRIBUSI PARKIR UNTUK PEMBERDAYAAN MASYARAKAT (STUDI PADA LEMBAGA PEMBERDAYAAN MASYARAKAT KELURAHAN KUTA, KECAMATAN KUTA) - Nofitasari, Juwita Vamellia; Bandiyah, Bandiyah; Wismayanti, Kadek Wiwin Dwi (CITIZEN CHARTER, 2016)
ABSTRACT Parking is a common problem in many area, but parking as one of potential incomes parking is not manage well. Badung Regency as one of potential tourism areas in Bali, especially in Kuta district also face the difficulty in which the volume of vehicles are not balance with the parking lot. Research method that used in this research is descriptive qualitative. To collect the data, the researcher did the field observation and deep interview with the interviewees who to know the information about the parking retribution management and public empowerment in Kuta district. The result from this research are : first, LPM Kuta as parking organizer get profit from parking retribution where by parking retribution that they got, LPM can empowering the people and The Department of transportation, communication and informatics as a coordinator, facilities and infrastructure provider and supervisory management. Second, there are some problems such as parking officer’s fraudulence. The parking officers toke the return by increasing the parking fees and not gave the parking ticket. Third, the income from parking retribution already use by the LPM to empowering the society but still less optimal on empowered the disability. Hopefully, by this research both the government and LPM can monitoring the parking management in field and the disability get the special treat Key words: society empowerment, cooperation, parking retribution